2013
DOI: 10.1103/physreve.88.012118
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-equilibrium one-dimensional disordered dipole chain

Abstract: We consider a chain of one-dimensional dipole moments connected to two thermal baths with different temperatures. The system is in nonequilibrium steady state and heat flows through it.Assuming that fluctuation of the dipole moment is a small parameter, we develop an analytically solvable model for the problem. The effect of disorder is introduced by randomizing the positions of the dipole moments. We show that the disorder leads to Anderson-like transition from conducting to a thermal insulating state of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
2
1
0
Order By: Relevance
“…11 Related effects had been observed in early experiments by Lehman, shortly after the discovery of liquid crystals (LC), who showed that the average molecular orientation of the anisotropic LC can be modified by applying a thermal gradient. 12 It has also been shown very recently that thermal gradients induce long-range order in onedimensional dipole chains, 13 a result that is consistent with the theory and simulations discussed in ref 11. In the particular case of water, a highly polar fluid, it was demonstrated that the reorientation leads to an electrostatic field, which scales with the magnitude of the thermal gradient. A nonequilibrium analysis of this problem shows that the field varies linearly with the thermal gradient and inversely with temperature and also depends on the polarity of the liquid through the dielectric permittivity and the so-called phenomenological coefficients, which measure the dipole moment correlation time of the sample and the coupling between the heat flux and the polarization.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…11 Related effects had been observed in early experiments by Lehman, shortly after the discovery of liquid crystals (LC), who showed that the average molecular orientation of the anisotropic LC can be modified by applying a thermal gradient. 12 It has also been shown very recently that thermal gradients induce long-range order in onedimensional dipole chains, 13 a result that is consistent with the theory and simulations discussed in ref 11. In the particular case of water, a highly polar fluid, it was demonstrated that the reorientation leads to an electrostatic field, which scales with the magnitude of the thermal gradient. A nonequilibrium analysis of this problem shows that the field varies linearly with the thermal gradient and inversely with temperature and also depends on the polarity of the liquid through the dielectric permittivity and the so-called phenomenological coefficients, which measure the dipole moment correlation time of the sample and the coupling between the heat flux and the polarization.…”
Section: Introductionsupporting
confidence: 80%
“…Related effects had been observed in early experiments by Lehman, shortly after the discovery of liquid crystals (LC), who showed that the average molecular orientation of the anisotropic LC can be modified by applying a thermal gradient . It has also been shown very recently that thermal gradients induce long-range order in one-dimensional dipole chains, a result that is consistent with the theory and simulations discussed in ref . In the particular case of water, a highly polar fluid, it was demonstrated that the reorientation leads to an electrostatic field, which scales with the magnitude of the thermal gradient.…”
Section: Introductionsupporting
confidence: 72%
“…A lattice chain of dipoles which interact and rotate is known in context of other studies, see, e.g., Ref. [29].…”
Section: Lattice Model Which Accounts For Interactions and Rotations ...mentioning
confidence: 99%